Spotted Gar and the Evolution of Innate Immune Receptors. Issue 7 (24th May 2017) - Wcisel, Dustin J.; Ota, Tatsuya; Litman, Gary W.; Yoder, Jeffrey A.
ABSTRACT: The resolution of the gar genome affords an opportunity to examine the diversification and functional specialization of immune effector molecules at a distant and potentially informative point in phylogenetic development. Although innate immunity is effected by a particularly large number of different families of molecules, the focus here is to provide detailed characterization of several families of innate receptors that are encoded in large multigene families, for which orthologous forms can be identified in other species of bony fish but not in other vertebrate groups as well as those for which orthologs are present in other vertebrate species. The results indicate that although teleost fish and the gar, as a holostean reference species, share gene families thought previously to be restricted to the teleost fish, the manner in which the members of the multigene families of innate immune receptors have undergone diversification is different in these two major phylogenetic radiations. It appears that both the total genome duplication and different patterns of genetic selection have influenced the derivation and stabilization of innate immune genes in a substantial manner during the course of vertebrate evolution. GRAPHICAL ABSTRACT: The recently published genome of the spotted gar allows for novel inter‐species comparisons. Gar reveals the ancient origins of multiple innate immune gene families and their diverse utilization across divergent vertebrate lineages.